An Examination of Modelling, Simulation and Detection of Fault Behaviours in HVDC Monopolar System - Ikotun, Olumoroti; Shehu, Suleiman (Asian Journal of Computing and Engineering Technology, 2023)
Purpose: Some previous researchers work on the HVDC Monopolar systems using Matlab/Simulink environment to carry out their analyses. We continue this discussion of Monopolar HVDC systems. Methodology: The analyses that are carried out include double phase-to-ground fault, single phase-to-ground fault and three phase-to-ground fault at the AC side of the rectifier and the DC line to ground fault. Findings: It is discovered, among others, that for three phase-to-ground fault, the voltages at the AC side of the rectifier, the DC line voltage and the voltage at the inverter side of the load are completely zero but that the current in the rectifier will increase from its standard value though will be less harmful and the current of the inverter side will decrease from its original value. It is further discovered that the fastest transient will be the case when fault is applied to the DC transmission system and that transmission network is of critical importance in high voltage transmission lines and engineers can also use this result to identify different faults in the transmission lines and the care of power quality is highly important because of electrical energy demand. Unique Contribution to Theory, Practice and Policy: The current in the rectifier decreases from its standard value but will be less harmful. The causes of decrease in DC transmission line depend on severity of the fault such as single phase to ground, double line to ground and three phase-to ground at the rectifier side.